2019
DOI: 10.1002/jgc4.1116
|View full text |Cite
|
Sign up to set email alerts
|

Rapid clinical exome sequencing in a pediatric ICU: Genetic counselor impacts and challenges

Abstract: Exome sequencing (ES) has revolutionized molecular diagnosis in children with genetic disease over the past decade. However, exome sequencing in the inpatient setting has traditionally been discouraged, in part due to an increased risk of providers failing to retrieve and act upon results, as many patients are discharged before results return. The development of rapid turn‐around‐times (TATs) for genomic testing has begun to shift this paradigm. Rapid exome sequencing (rES) is increasingly being used as a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…The implications of secondary findings for the individual and other family members also needs discussion before parents decide. As observed previously, some parents preferred to defer decisions on secondary findings, while others opted in so they had the chance to address health concerns [ 30 ]. We also found that parents, particularly those without a diagnosis, may want more information on certain topics, such as which genes had been tested and whether reanalysis would be available to them in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of secondary findings for the individual and other family members also needs discussion before parents decide. As observed previously, some parents preferred to defer decisions on secondary findings, while others opted in so they had the chance to address health concerns [ 30 ]. We also found that parents, particularly those without a diagnosis, may want more information on certain topics, such as which genes had been tested and whether reanalysis would be available to them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additional training is needed alongside support from genetics colleagues for decisions on eligibility, interpretation of results and counselling. A potential role for genetic counsellors in delivering RGS in ICUs has been suggested, as they are well placed to support the information and emotional needs of parents [ 10 , 12 , 30 ], and this should be explored as we deliver RGS in the UKs Genomic Medicine Service.…”
Section: Discussionmentioning
confidence: 99%
“…Stark et al found similar results in a study of Australian critical care providers who strongly preferred that rapid genomic testing in the acute pediatric setting to be led by clinical genetic services (Stark et al, ). Previous studies have highlighted the roles of genetic counselors in critical care settings with a focus on patient support (Ayres et al, ; Clowes Candadai, Sikes, Thies, Freed, & Bennett, ). Genetic counselors can allow for long‐term follow‐up and continuity of care surrounding genetic results.…”
Section: Discussionmentioning
confidence: 99%
“…They also provide psychosocial support for families in crisis, especially surrounding life‐limiting diagnoses and the initiation of palliative care. Genetic counselors also ensure that other implications of genetic testing, such as incidental findings, are considered in high‐stress environments (Ayres et al, ; Clowes Candadai et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation